An unusual benzoisoquinoline-9-one derivative and other related compounds with antiproliferative activity from Hawaiian endophytic fungus Peyronellaea sp. FT431 - Li, Chunshun (2019)
A new polyketide containing the benzoisoquinoline-9-one moiety, peyronetide A (1), and three other new derivatives peyronetides B–D (2–4), as well as one known compound (5) were purified from the cultured broth of the endophytic fungus Peyronellaea sp. FT431, which was isolated from the Hawaiian indigenous plant, Verbena sp. The structures of the new compounds were determined through the analysis of HRMS and NMR spectroscopic data. Compounds 1, 2, and 5 showed cytotoxic activities against TK-10 (human kidney adenocarcinoma cells), cisplatin sensitive A2780S (human ovarian carcinoma cells), and cisplatin resistant A2780CisR cell lines, with IC50 values between 6.7 to 29.2 µM.